Relationship of urinary excretion of calcium and phosphates and spirometric parameters in children with bronchial asthma - A. D. Yudina; S. V. Vanyakina; E. V. Tush; T. I. Eliseeva; A. N. Obukhova; D. V. Baratynskiy; N. Yu. Geraskina; A. V. Stroganov; O. V. Khaletskaya (Аллергология и Иммунология в Педиатрии, 2023)
.